EXTENSION PROJECT “CURSINHO POPULAR PAULO FREIRE” IN BRAGANÇA, PARÁ, AMAZON: structure, results, challenges and potentialities (Citizenship in Action: Extension and Culture Magazine, 2025)
The objective of this paper is to report on the extension activities of the Paulo Freire Popular Prep Course (CPPF) to ensure access to higher education. The CPPF extension project aims to democratize access to higher education for young people and adults in the municipality of Bragança and surrounding areas who are in situations of social vulnerability, preparing them for the selection processes of public universities/institutes. The perspective adopted by the course is Freirean, aiming to socially transform the students' reality through education, thus promoting critical thinking about the importance of education and its relationship with society. The CPPF is currently linked to the "Transversal Axis" extension call for proposals from the Extension Pro-Rectorate (PROEX) of the Federal University of Pará, which funds an extension scholarship from August 2018 to July 2020. The CPPF has two target audiences, with young people and adults from Bragança in social vulnerability preparing for the National High School Exam (ENEM) being the main focus. The CPPF has been an extension project since 2007, with significant results in university entrance exam approvals. From a sample of the years 2016 to 2018, forty-nine students were approved: ten from the 2016 class, twenty-seven from the 2017 class, and twenty-two from the 2018 class. These numbers represent an annual approval rate of just over 50% per class. One of the main challenges faced by the prep course is the learning difficulties, particularly among students from public basic education. There are challenges surrounding the students' learning in preparation for the ENEM that need to be jointly addressed by the CPPF, the University, and public schools so that the CPPF extension project becomes more effective each year. The CPPF is of great importance in its objectives within the local context, both in terms of preparing and approving students in the ENEM, and as a space for pedagogical and didactic practice for undergraduate students.